Media Influence on Public Policy in Kenya: The Case of Illicit Brew Consumption - Christine Mwangi (SAGE Open, 2018)
The media plays a major role in public life, influencing citizens’ focus of attention and providing many of the facts and opinions that shape perspectives on topics of the day. Studies that analyze media influences on policy making have had mixed results on whether the media does actually influence public policy. This case study analyzes the role of the media in Kenya in influencing public policy in relation to illegal brew sale and consumption. The study seeks to understand media coverage mechanisms that led to government actions on an issue. This was done through content analysis of the coverage in two leading daily newspapers over a period of 10 years (2005-2015). The analysis found that intense, congruent, and incident-driven media coverage had influence on government action and consequently public policy on the issue. The findings also found weaknesses in media reporting. The media was very good at telling the politicians what was happening and what to talk about, but they were less able to tell the politicians what to do, which compromised the watchdog role of the media in Kenya. These findings can also be useful for advocacy groups and the public on the ways to engage the media to influence policy makers’ decisions.